The Effect of Work Motivation, Work Discipline and Work Environment on the Performance of ASN Employees at the North Sumatra Provincial Education Office - David Christian Tambun; Prem Raaj; Dita Ibrena Luluina Br Tarigan; Melfrianti Romauli Purba; Nasib Nasib (SEAN Institute, 2026)
This study aims to determine the influence of work motivation, work discipline, and the work environment on the performance of civil servant employees at the North Sumatra Provincial Education Office. Employee performance is a crucial factor in improving the quality of public services and achieving organizational goals. Therefore, supporting factors such as high work motivation, good work discipline, and a conducive work environment are needed to improve employee performance. The research method used was a quantitative survey approach. Data collection was conducted by distributing questionnaires to 88 respondents, who were civil servant employees at the North Sumatra Provincial Education Office. The data obtained were analyzed using multiple linear regression analysis with the assistance of statistical software. The results of this study indicate that motivation has a negative and insignificant effect on employee performance, work discipline has a positive and significant effect on employee performance, and the work environment has a positive and significant effect on employee performance. Simultaneously, motivation, discipline, and the work environment have a significant effect on civil servant employee performance at the North Sumatra Provincial Education Office.